The ex ante incentive compatible core in the absence of wealth effects - Françoise Forges; Jean-François Mertens; Rajiv Vohra (Brown University, Department of Economics, 2001)
In a differencial economy with quasi-linear utilities, monetary transfers facilitate the fulfilment of incentive compability constraints: the associated ex ante core is generically nonempty. However, we exhibit a well-behaved exchange economy in which this core is empty, even if goods are allocated through random mechanisms.
Keywords: 330; Core; exchange economy; asymmetric information; incentive compability; ex ante; transferable utility; absence of wealth effects : quasi-linear; Core; Asymmetrische Information; Allgemeines Gleichgewicht; Ökonomischer Anreiz; Vermögenseffekt; Theorie